The impact of the economic crisis on the ideological space in Portugal and Greece: a comparison of elites and voters - Tsatsanis, E.; Freire, A.; Tsirbas, Y. (South European Society and Politics, 2014)
This work addresses the dimensions and content of ideological space in Portugal and Greece after the onset of the sovereign debt crisis and the imposition of austerity policies in the two countries. By examining both elite interviews and public opinion data, the article principally attempts to determine whether the economic crisis has created a new division in ideological space by cross-cutting or completely replacing older ones. In addition, we attempt to gauge the position of crisis-related issues relative to issue divides on European integration and globalisation which, up to now, have been dormant in Southern European countries